Overview of the Readiness of Banks, Regulations, Customers and Notaries in Facing the Transformation of Banking Digitalization - Mila Gemilang; Aad Rusyad Nurdin (Budapest International Research and Critics University, 2022)
The era of disruption requires banks to make significant changes, starting from procedures, working methods, organizational structures, and business models. Changes are not only incremental, but radical changes must be made to maintain the existence of the business, these changes must be carried out in synergy among stakeholders. The question that arises is the extent to which regulations, banks, customers and notaries are prepared to face the transformation of banking digitalization. In terms of regulation, Bank Indonesia and the Financial Services Authority (OJK) as government authorities have issued rules and guidelines for banks to face the transformation of banking digitalization by prioritizing aspects of Balance and Technology Neutral. According to the results of the Digital Maturity Assessment for Banks (DMAB), banks in Indonesia have a readiness level of around 50%. From the results of interviews with several banking executives, it was revealed that bank digitization cannot be carried out in all bank processes, but only in simple processes such as opening accounts and loans without collateral. On the other hand, the level of community readiness to use digital banking services is adequate, where 98.3% of internet users have mobile phones. However, it turns out that some people are reluctant to use e-banking services because of fears of failed transactions and legal protection for e-banking transactions. With regard to digital banking transformation, more complex transactions, for example those requiring the services of a Notary, cannot be carried out digitally because the bank credit agreement deed requires the presence of the parties and cannot use digital signatures which under the ITE Law cannot be used as legal evidence